Mine Scheduling of Lateritic Nickel Ore in The Mawar Block of PT Ang and Fang Brother Site Lalampu, Central Sulawesi Province, Indonesia - Anas, Aryanti Virtanti; Syaifullah, Nanda Syafriana; Amalia, Rizki; Sutardjo Tui, Rini Novrianti (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2024)
PT Ang and Fang Brothers planned to open a new pit of lateritic nickel ore in Mawar Block. Mine scheduling of open-pit mines is an important thing in surface mine planning so the purpose of this research is to provide an overview of pit design and mining sequences, amount of production and number of equipment allocated in each sequence. The production targeted by the company was 50,000 tons by considering the mine recovery factor of 90%. Mine scheduling requires several data, namely cycle time, loss time, block model, equipment specifications and availability, slope and mine haul road geometry, and topography. The data used to design pit limits, mining sequences, and production scheduling. Based on the design of the mine pit, the total overburden that must be removed is 365,589 bcm and the total laterite nickel ore that must be stripped is 169,240 tons with a stripping ratio of 2.2:1 which is divided into three mining sequences. Total tonnage of lateritic nickel ore in the first to the third sequence is 55,677 tons, 55,518 tons, and 58,045 tons with overburden of 143,764 bcm, 136,055 bcm, and 85,770 bcm respectively. The equipment fleet of the first to the third sequence is 4 units’ loader with 17 units’ hauler, 4 units’ loader with 17 units’ hauler, and 3 units’ loader with 13 units’ hauler respectively.